Authentic Learning Through Advances in Technologies (Lecture Notes in Educational Technology,, 2018)
This book introduces the advanced technologies used for authentic learning, an educational term that refers to a variety of techniques focusing on how students apply the skills and knowledge acquired in school in real-world situations. In the meanwhile, it presents the latest trends and future developments in learning design, learning environment and assessment for authentic learning using advances in technology, this book discusses how technology supports authentic learning and what makes it effective.